Age‐Dependent Effects of Muscle Resting Calcium on Fasting Blood Glucose: Implications for Prediabetes Risk - Eshwar R. Tammineni; Lourdes Figueroa; Michael Fill; Sheila Riazi; Carlo Manno (Endocrinology, Diabetes & Metabolism)
ABSTRACT Background and Aims Skeletal muscle is the primary site for insulin‐mediated glucose uptake and is critical in maintaining whole‐body glucose homeostasis. Muscle cells from malignant hyperthermia‐susceptible (MHS) individuals exhibit elevated resting cytosolic calcium concentration ([Ca2+]cyto), and MHS subjects have a higher incidence of hyperglycaemia. This study investigates the association between elevated resting [Ca2+]cyto and fasting blood sugar (FBS) levels while accounting for subject demographics and clinical variables. Methods We measured resting [Ca2+]cyto in myotubes derived from muscle biopsies of control and MHS subjects. We analysed the impact of [Ca2+]cyto on FBS levels based on age, sex, and MH status through correlation and comparative analyses. Data were stratified by FBS, [Ca2+]cyto, and age, and heat map and 3D mesh plot analyses were performed to assess the risk of prediabetes in subjects with varying [Ca2+]cyto and age. Results Between 2013 and 2024, muscle biopsies from 152 subjects (90 MHS, 62 controls) were used to establish primary myotube culture. MHS myotubes exhibited significantly higher resting [Ca2+]cyto than controls and [Ca2+]cyto positively correlated with fasting blood sugar (FBS) in MHS subjects (r = 0.227; p = 0.031) and across the entire cohort (r = 0.176; p = 0.034). This correlation was high in prediabetic individuals (r = 0.43; p = 0.005) but absent in those with normal FBS. Subjects over 40 years with [Ca2+]cyto > 150 nM showed a higher risk of prediabetes. While aging is a significant risk factor for type 2 diabetes, increased age did not impact FBS levels in individuals with [Ca2+]cyto below 150 nM. However, in those with [Ca2+]cyto exceeding 150 nM, increasing age significantly influenced FBS. Conclusions Elevated resting [Ca2+]cyto in skeletal muscle amplifies the risk of hyperglycemia and may contribute to the onset of type 2 diabetes.